2019
DOI: 10.1182/blood-2018-06-858415
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of carfilzomib-induced cardiotoxicity in mice and the emerging cardioprotective role of metformin

Abstract: Carfilzomib (Cfz), an irreversible proteasome inhibitor licensed for relapsed/refractory myeloma, is associated with cardiotoxicity in humans. We sought to establish the optimal protocol of Cfz-induced cardiac dysfunction, to investigate the underlying molecular-signaling and, based on the findings, to evaluate the cardioprotective potency of metformin (Met). Mice were randomized into protocols 1 and 2 (control and Cfz for 1 and 2 consecutive days, respectively); protocols 3 and 4 (control and alternate doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
123
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(141 citation statements)
references
References 59 publications
16
123
2
Order By: Relevance
“…In particular, the agent is associated with cardiovascular AEs. Recently, Efentakis et al demonstrated that cardiotoxicity by carfilzomib is associated with the autophagy pathway and upregulation of protein phosphatase (PP)-2A phosphatase activity but not the inhibition of the proteasome function [60]. Selected carfilzomib-containing regimens for relapsed and/or refractory MM patients are shown in Table 4.…”
Section: Carfilzomibmentioning
confidence: 99%
“…In particular, the agent is associated with cardiovascular AEs. Recently, Efentakis et al demonstrated that cardiotoxicity by carfilzomib is associated with the autophagy pathway and upregulation of protein phosphatase (PP)-2A phosphatase activity but not the inhibition of the proteasome function [60]. Selected carfilzomib-containing regimens for relapsed and/or refractory MM patients are shown in Table 4.…”
Section: Carfilzomibmentioning
confidence: 99%
“…However, speculations can be made on its irreversible and highly potent proteasome inhibition activity that could differentiate its safety profile from that of bortezomib . Cardiac stress produces misfolded proteins; proteasome‐mediated degradation of these toxic products is pivotal to preserve cellular function in some patients . Moreover, the levels of nitric oxide, an important mediator of endothelial function, could also be modulated by proteasome activity, and decreased nitric oxide levels could impair vasodilatation, inducing hypertension and cardiac dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…Although the underlying pathomechanism has not been elucidated, proteasome inhibitor-associated perturbation of endothelial nitric oxide synthase (eNOS) has been hypothesized to facilitate cardiovascular dysfunction [21]. Additionally, a direct effect on cardiac protein homeostasis has been demonstrated in a preclinical model [22]. Risk factors for cardiotoxicity (e.g., diabetes mellitus, poorly controlled arterial hypertension, known history of heart failure) should be assessed at baseline.…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
“…Elevation of BNP (>400 pg/ml) is associated with higher rates of hospitalization for cardiovascular adverse events [21]. Metformin may exhibit a preventive effect, but prospective clinical data are still warranted [22].…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%